Governance and Administration Systems in the Kingdom of Castile - Obeid, Dr. Mahmoud Ashour (Thi Qar Arts Journal, 2024)
Governance and administration systems form an essential part of the foundation and development of every state. This is particularly true for the Spanish Christian kingdoms, including the Kingdom of Castile, which were newly established. The emergence and class diversity, along with the ongoing conflict with Muslims, necessitated the issuance of systems and laws compatible with the kingdom’s structure. This research briefly addresses the governance and administration systems in the Kingdom of Castile, focusing on the system of governance, the royal council, and the key laws issued by the kings of Castile to organize their kingdom’s affairs and legislate judicial laws. Additionally, the research covers education in the Kingdom of Castile and the translation movement, especially during the reign of King Alfonso X. Finally, the research touches on the currency that was in circulation in the Kingdom of Castile.   Shortly after the Muslims entered Andalusia, the Spanish Christian kingdoms began to emerge and gradually develop. This emergence and development were accompanied by the re-establishment of systems, laws, rulings, and state institutions. Some of these laws and administrative systems were inherited from the Visigothic Kingdom, which fell with the Muslim conquest, while others were imposed by new political and religious circumstances over time. These laws and systems contributed, in one way or another, to the political and cultural development of the Spanish kingdoms, aiding in their internal stability, albeit relatively. Often, these laws and systems conflicted with the interests of the nobility, leading to a kind of power struggle with them.